Obesity is common at diagnosis of childhood pituitary adenoma and may persist following successful treatment. (19th January 2020) - Sethi, Aashish; Didi, Mohammed; Dharmaraj, Poonam; Ramakrishnan, Renuka; Senniappan, Senthil; Das, Urmi; Avula, Shivaram; Sinha, Ajay; Mallucci, Conor; Weerasinghe, Kamal; Daousi, Christina; Gilkes, Catherine; et al.
Abstract: Objective: There is a paucity of data describing long‐term outcomes of paediatric patients with pituitary adenoma. In this report, we describe clinical features, treatment and outcomes of a paediatric cohort. Design: Retrospective cohort study. Patients: Twenty‐four white Caucasian patients aged <16 years from a single tertiary care centre in the United Kingdom at diagnosis followed for (median, range) 3.3, 0.7‐8.4 years. Measurements: Clinical and radiological data at diagnosis and follow‐up. Results: Thirteen patients had prolactinomas (54.1%, age: 15.2 years, 13.2‐15.8 years; all females), including ten macroadenomas (11.0‐35.0 mm). Patients presented with menstrual disorders (91%), headache (46%), galactorrhoea (46%) and obesity (body mass index [BMI] SDS > 2): (38%). Ten patients with prolactinoma were treated with dopamine agonist alone, 3 also required surgery and 2 patients, cabergoline, surgery plus radiotherapy. Five patients had Cushing's disease (20.8%, age: 14.0, 4.0‐15.7 years; 2 female), including one macroadenoma (24 mm). Patients presented with obesity (100%), short stature (60%) and headache (40%). Transsphenoidal resection resulted in biochemical cure (09.00 cortisol < 50 nmol/L). Two patients relapsed 3‐ and 6 years following surgery, requiring radiotherapy. One patient also required bilateral adrenalectomy. Six patients had nonfunctioning pituitary adenoma (25.0%, age: 15.8, 12.5‐16.0 years; 2 female), including two macroadenomas (20.0‐53.0 mm). Patients presented with obesity (67%), visual field defects (50%) and headache (50%). Four required surgical resections; two recurred following surgery and required radiotherapy. On latest follow‐up; 13 (54.1%) patients were obese (BMI 3.09 SDS; range: 2.05‐3.73 SDS). Conclusion: Obesity is common at diagnosis of pituitary adenoma in childhood and may persist despite successful treatment. Adenomas were larger, more resistant to treatment, and more likely to recur than in adult populations.